2001
DOI: 10.1107/s0909049500013753
|View full text |Cite
|
Sign up to set email alerts
|

Iodine L-edge XAFS study of linear polyiodide chains in amylose and α-cyclodextrin

Abstract: We performed iodine L edge XAFS measurements on blue-black amylose-iodine complex to obtain information about the electronic and geometrical structures of polyiodide chain included in amylose helix. Measurements were also carried out on crystalline «-cyclodextrin-iodine complex («-cyclodextrin)2¡Cd0 5¡I5¡27H2 O, in which the polyiodide chain is known to consist of I 5 unit. It was found that the XANES spectra of these complexes have similar line shapes except for some minor differences, indicating that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…5p transition of an iodine atom. [15] This observation is Figure 1. Electric-stimuli-responsive porous materials.…”
Section: Cpp (Figure 2c)mentioning
confidence: 79%
See 1 more Smart Citation
“…5p transition of an iodine atom. [15] This observation is Figure 1. Electric-stimuli-responsive porous materials.…”
Section: Cpp (Figure 2c)mentioning
confidence: 79%
“…[15] This result showed that the above-mentioned antibonding molecular orbitals were being occupied, that is,i odine molecules should receive electrons from the anode or CPP,though its valence value is not clear. …”
Section: Cpp (Figure 2c)mentioning
confidence: 99%
“…This improved performance most probably results from the structural flexibility of the amylose, facilitating its penetration into the film pores and adsorption to the dye sensitized film surface, consistent with previous studies which have reported greater flexibility of amylose relative to cyclodextrin in forming inclusion complexes. [24] The inclusion of amylose in the device structure does not appear to impact detrimentally on device stability. Indeed prolonged storage trials (over one month) indicated improved stability of devices including the amylose layer relative to control devices.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in iodine molecules or polyiodide ions where the 5pσ* molecular orbital is not completely filled, iodine l I -edge X-ray absorption spectra shows a sharp peak at the absorption threshold, which corresponds to iodine 2s → 5pσ* transition, and the intensity of this peak can be a quantitative measure of the valency of the iodine/iodide species in the sample under study [51]. It is also possible to determine the three-dimensional local structure around the X-ray-absorbing iodine atom as well as the electronic structure by performing multiple-scattering XAnes calculation from structural models and comparing the calculated spectra with the experiment [52][53][54].…”
Section: X-ray Absorption Spectroscopic Analysis Of Iodine and Iodidesmentioning
confidence: 99%